x alone divides into 2x^3 2x^2 times. Multiplying x+1 by 2x^2 gives 2x^3+ 2x^2:
(2x^3+ 5x^2- 2x- 3)- (2x^3+ 2x^2)= 3x^2- 2x- 3.
x alone divides into 3x^2 3x times. Multiplying x+1 by 3x gives 3x^2+ 3x:
(3x^2- 2x- 3)- (3x^2+ 3x)= -5x- 3.
x alone divides into -5x -5 times. Multiplying x+1 by -5 gives -5x- 5:
(-5x-3)- (-5x-5)= 2.
(2x^3 + 5x^2 - 2x - 3) / (x +1)= 2x^2+ 3x- 5 with remainder 2.
2x divides into 2x^3 x^2 times. Multiplying 2x-3 by x^2 gives 2x^3- 3x^3:b) (2x^3 - 7x^2 + 16x - 22) / (2x - 3)
(2x^3- 7x^2+ 16x- 22)- (2x^3- 3x^2)= -4x^2+ 16x- 22.
Can you finish that one?